2013
DOI: 10.1016/j.ijpsycho.2012.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Personality and physiological reactions to acute psychological stress

Abstract: Stable personality traits have long been presumed to have biological substrates, although the evidence relating personality to biological stress reactivity is inconclusive. The present study examined, in a large middle aged cohort (N=352), the relationship between key personality traits and both cortisol and cardiovascular reactions to acute psychological stress. Salivary cortisol and cardiovascular activity were measured at rest and in response to a psychological stress protocol comprising 5min each of a Stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
144
7
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(165 citation statements)
references
References 83 publications
12
144
7
2
Order By: Relevance
“…2). Recent research on the Big Five personality variables has found that individuals high on neuroticism and low on agreeableness exhibit blunted stress reactivity based on measures of salivary cortisol, HR, and blood pressure (Bibbey et al, 2013). The current HRV-based stress assessment raises questions about the possibility of Perfectionists exhibiting a similarly blunted stress reactivity as seen with other distressed personality factors.…”
Section: Discussionmentioning
confidence: 88%
“…2). Recent research on the Big Five personality variables has found that individuals high on neuroticism and low on agreeableness exhibit blunted stress reactivity based on measures of salivary cortisol, HR, and blood pressure (Bibbey et al, 2013). The current HRV-based stress assessment raises questions about the possibility of Perfectionists exhibiting a similarly blunted stress reactivity as seen with other distressed personality factors.…”
Section: Discussionmentioning
confidence: 88%
“…The acute response to the stressor is then induced in the limbic system where the subjective evaluation of this stimulus takes place in the context of the individual coping capacity [33] and the respective personality traits [34]. The physiological response to such a stressor is structured in 2 successive processes.…”
Section: Resultsmentioning
confidence: 99%
“…Personality determines a person's reaction to stress. 20 Stress can lead to an increasing sympathetic muscle tone. This condition also triggers adrenaline release leading to constriction of blood vessels.…”
Section: Kusmiyati Et Al Extrovert Personality Type and Prolonged Sementioning
confidence: 99%